The Impact of Celebrity Fan Club towards the Willingness to Stay at Hotel XYZ - Armando Armando (iBuss Management, 2014)
Tourism industry is one of the most important industry in Indonesia. In Jakarta, five-star hotel has been one of the most promising business. This research is done to know the impact of Celebrity Fan Club campaign towards the willingness to stay at Hotel XYZ. The four source models, which are source credibility model, source attractiveness model, product match-up model and meaning transferability model, are elements that are used to measure the campaign which will impact the willingness to stay. The sample that the author use is anyone who has experienced staying in five-star hotels. There are 76 samples that was gathered in this research using simple random sampling method. The analysis technique that is used in this research is multiple linear regression to know the relationship between the Celebrity Fan Club which is a celebrity endorsement towards the willingness to stay. The research result shows that Celebrity Fan Club significantly impact the willingness to stay. Keywords: Source, Celebrity Endorsement, Willingness to Stay, Celebrity Fan Club and Branding.